2006
DOI: 10.1111/j.1440-1681.2006.04507.x
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical Evaluation of Antidiabetogenic Properties of Some Commonly Used Indian Plants on Streptozotocin‐induced Diabetes in Experimental Rats

Abstract: 1. Diabetes mellitus is a serious metabolic disorder with micro- and macrovascular complications that results in significant morbidity and mortality. 2. The aim of the present study was to evaluate the hypoglycaemic efficacy of commonly used traditional Indian plants, such as Murraya koenigii, Mentha piperitae, Ocimum sanctum and Aegle marmelos, in streptozotocin (STZ)-induced experimental rats. 3. Oral administration of the ethanolic extract of these plants resulted in a significant decrease in the levels of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
56
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(61 citation statements)
references
References 46 publications
5
56
0
Order By: Relevance
“…to increase in diabetic specimens and decrease with antidiabetic treatment (Stanely et al, 2000;Narendhirakannan et al, 2006). In sum, it seems likely that even juvenile viscachas kept on the old diet were in the initial metabolic stages of T2DM.…”
Section: Resultsmentioning
confidence: 99%
“…to increase in diabetic specimens and decrease with antidiabetic treatment (Stanely et al, 2000;Narendhirakannan et al, 2006). In sum, it seems likely that even juvenile viscachas kept on the old diet were in the initial metabolic stages of T2DM.…”
Section: Resultsmentioning
confidence: 99%
“…There are many studies pertaining to the effect of phytochemicals, such as flavonoids, on diabetes (Narendhirakannan et al, 2006). Phytochemical studies have identified more than 20 compounds in guava fruit extract (Begum et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…However, search for new antidiabetic drugs continue. Although the leaves and fruits of A. marmelos were studied widely for their antidiabetic activity (Narendrakannan et al, 2006;Kesari et al, 2006), the reports on antidiabetic activity of roots are limited. The present study was aimed at investigating the antidiabetic effect of A. marmelos and identifying the active principles.…”
Section: Introductionmentioning
confidence: 99%